TOPICAL ANALGESIC ACTIVITY OF ESSENTIAL OIL EXTRACTED FROM SPHARENTHUS INDICUS (ASTERACEAE) - Padhan, Dipti Kanta; Sriballav, Patel; Arnabaditya, Mohanty (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate the topical analgesic effects of essential oil extracted from Spharenthus indicus (Asteraceae). Methods: The essential oil was extracted from fresh flower of Spharenthus indicus. Topical ointment containing essential oil was investigated for analgesic activity in rat using hot plate method. Diclofenac sodium gel was taken as standard drug. Result: The analgesic activity of topical preparation was observed in the early phase. The analgesic activity of topical preparation showed significant activity comparative to standard drug diclofenac sodium. Conclusion: Hence the study validates the traditional use of Spharenthus indicus to relive pain. Â 